Factors Affecting Job Satisfaction of Employees in Government Sector Organizations - Shiv Kumar Tripathi; Dr. Ramesh Kumar Chaturvedi (International Journal of Engineering and Management Research, 2023)
Job may be defined as a specific task done as part of the routine of one's occupation or for an agreed price. Job is a social expectation and social reality to which people seem to confirm for maintaining their livelihood. It not only provides status and psychological satisfaction to the individuals but also binds them to the society. Job satisfaction is a person’s attitude towards the job. Job satisfaction means measurement of excellence to which an employee feels contended and happy about his work and the conditions in which it has to be done. The main purpose of the study is to investigate the determinants like encouragement, management, working condition and training as the various facets of employee job satisfaction which plays a major role for employee performance. A quantitative approach is used in this study. A Pearson correlation research design and survey method is used to collect data. A research model and four hypotheses were developed. Regression analysis was used to test the hypotheses. The study found the implementation of independent variables like encouragement, management, working condition and training by public sectors enterprises. for maintaining the job satisfaction of employees in the organization. All of the predictor variables were significantly related to the success of employee performance.